A Case of Right Posterior Semicircular Canal Benign Paroxysmal Positional Vertigo with to-and-fro Canal Switch to Right Horizontal Semicircular Canal - Vats, Ajay Kumar (Annals of Otology and Neurotology, 2020)
Background Canal switch in BPPV is a phenomenon occurring after therapeutic canalith repositioning maneuvers (CRM), when there is a reflux of the repositioned otoconial debris from utricle to semicircular canal other than the one originally affected. It may be of immediate-type occurring within minutes after CRM or a delayed-type occurring after 2-3 days.Aim The study is a case report.Case Report A 59-year-old female presented with history of severe rotational vertigo as she got up from the bed in the early morning at 5.00 a.m.. Dix-Hallpike test (DHT) on the right elicited an upbeating positional nystagmus (PN). Treatment with multiple consecutive modified right Epley maneuvers (r-MEM) in one session was undertaken. During these maneuvers she continued to have an upbeating PN during the 45-degrees right cervical rotation with the neck in 20-degrees of extension (which is equivalent to right Dix-Hallpike positioning) of the first three sequential r-MEM’s. With the neck maintained in 20-degrees of extension, during fourth consecutive r-MEM, the 45-degrees cervical rotation to right elicited apogeotropic horizontal PN. Supine roll test (SRT) was immediately undertaken. Maximal head yaw positioning to right as well as to the left elicited apogeotropic horizontal PN without torsional component lasting more than one minute, indicating reflux of otoconia from the right P-SCC to the short anterior arm of right H-SCC. She was treated with two sequences of Appiani maneuver and SRT one hour later elicited geotropic upbeating PN with vertigo, indicating second canal switch to P-SCC. It was successfully treated with two sequences of right EM fifteen minutes apart, with instructions to stay upright in between and after the maneuvers. At 24 hours, repeat DHT and SRT were negative and patient was asymptomatic.Conclusion An optimal time delay to perform a verifying positional test after therapeutic session with CRM is crucial to prevent the immediate type of reflux of relocated otoconia from the utricle into a different semicircular canal. In centers, where more than a single EM is performed in a single session of treatment, a delay of 10 to 15 minutes appears to be appropriate between successive maneuvers. A certain period of restraint in the vertical position after CRM may prevent immediate reflux, but this needs to be confirmed by the randomized control trials.
Keywords: canal switch; canalolithiasis; Epley’s maneuver; supine roll test; canalith repositioning maneuver; positional nystagmus